2016
DOI: 10.2106/jbjs.15.01329
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Prevalence of and Risk Factors for Venous Thromboembolism in Patients with a Hip Fracture

Abstract: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
5
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(107 citation statements)
references
References 24 publications
6
90
5
6
Order By: Relevance
“…22 Similarly, patients with traumatic hip fractures are at higher risk for VTE both preoperatively and postoperatively. 23,24 The increased risk is mediated by immobility during and after the surgery as well as by direct venous injury and inflammation during surgery. Pharmacologic thromboprophylaxis is preferred over mechanical thromboprophylaxis and reduces the incidence of DVT and PE in the postoperative period.…”
Section: Acquired Risk Factorsmentioning
confidence: 99%
“…22 Similarly, patients with traumatic hip fractures are at higher risk for VTE both preoperatively and postoperatively. 23,24 The increased risk is mediated by immobility during and after the surgery as well as by direct venous injury and inflammation during surgery. Pharmacologic thromboprophylaxis is preferred over mechanical thromboprophylaxis and reduces the incidence of DVT and PE in the postoperative period.…”
Section: Acquired Risk Factorsmentioning
confidence: 99%
“…There are few studies that directly identify the incidence and importance of DVT in the uninjured limb in patients with lower extremity fractures. Most previous research analysed the distribution of DVT in the injured limb across the different fractures [3], or risk factors contributing to a DVT in the injured limb during the hospital stay [8]. Song et al [5] reported the changes in DVT in the injured limb in 119 patients and found a high incidence of preoperative DVT in patients [5].…”
Section: Discussionmentioning
confidence: 99%
“…The delay may result from preoperative medical evaluation and optimization or transfer from community hospitals to tertiary-care facilities. Elderly patients tend to be sicker on admission and therefore more likely to require more time for preoperative preparation [8,9]. The delays in surgical intervention may predispose patients to developing thromboembolic problems and may be related to the uninjured limb thromboembolic problems.…”
Section: Discussionmentioning
confidence: 99%
“…В некоторых из этих публикаций рассматриваются венозные тромбозы, развившиеся до операции, с оценкой их частоты. Лишь единичные публикации о предоперационных венозных тромбозах у пациентов с патологией опорно-двигательного аппарата сообщают о возможности операции после проведения антикоагулянтной терапии или имплантации кава-фильтра, но не содержат четких указаний, в каких ситуациях это целесообразно [15,16].…”
Section: Discussionunclassified